Isolated Metastatic Carcinoma to the Hamate Bone: The First Manifestation of an Occult Malignancy - Tabrizi, Ali; Afshar, Ahmadreza; Shariyate, Mohammad Javad; Gharalari, Farzaneh Hosseini; Aidenlou, Ali (Journal of Hand and Microsurgery, 2019)
A 60-year-old man presented with swelling, pain, and tenderness at the ulnar side of his left wrist. Imaging studies demonstrated an osseous lesion in the left hamate bone. Histopathology study of the lesion revealed that the lesion was an isolated osseous metastatic carcinoma. The metastasis was the first presentation of this occult malignancy. The patient was treated with radiotherapy and chemotherapy; however, he expired 20 months after the diagnosis. This is a level IV study.
Keywords: Keywords; acrometastasis; carpal metastasis; hamate; hand metastasis; wrist metastasis